The characteristics and roles of β‐TrCP1/2 in carcinogenesis. (23rd October 2020) - Bi, Yanli; Cui, Danrui; Xiong, Xiufang; Zhao, Yongchao
Abstract : β‐transducin repeat‐containing protein (β‐TrCP), one of the well‐characterized F‐box proteins, acts as a substrate receptor and constitutes an active SCF β‐TrCP E3 ligase with a scaffold protein CUL1, a RING protein RBX1, and an adaptor protein SKP1. β‐TrCP plays a critical role in the regulation of various physiological and pathological processes, including signal transduction, cell cycle progression, cell migration, DNA damage response, and tumorigenesis, by governing burgeoning amounts of key regulators for ubiquitination and proteasomal degradation. Given that a variety of β‐TrCP substrates are well‐known oncoproteins and tumor suppressors, and dysregulation of β‐TrCP is frequently identified in human cancers, β‐TrCP plays a vital role in carcinogenesis. In this review, we first briefly introduce the characteristics of β‐TrCP1, β‐TrCP2, and SCF β‐TrCP ubiquitin ligase, and then discuss SCF β‐TrCP ubiquitin ligase regulated biological processes by targeting its substrates for degradation. Moreover, we summarize the regulation of β‐TrCP1 and β‐TrCP2 at multiple layers and further discuss the various roles of β‐TrCP1 and β‐TrCP2 in human cancer, functioning as either an oncoprotein or a tumor suppressor in a manner dependent of cellular context. Finally, we provide novel insights for future perspectives on the potential of targeting β‐TrCP1 and β‐TrCP2 for cancer therapy. Abstract : SCF β‐TrCP ubiquitin ligase plays a critical role in the regulation of various physiological and pathological processes by governing key regulators for ubiquitination and proteasomal degradation. Its activity is tightly controlled at multiple layers, including multiple signaling pathways, miRNAs, and lncRNAs. A variety of β‐TrCP substrates are well‐known oncoproteins and tumor suppressors, and dysregulation of β‐TrCP is frequently identified in human cancers. Therefore, β‐TrCP plays cellular context‐dependent tumor‐suppressing or tumor‐promoting roles in carcinogenesis.